Kierunki „migracji naukowych” niemieckich profesorów związanych z Wydziałem Prawa Uniwersytetu Wrocławskiego w latach 1811–1945 - Dolata, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In the article the author examines the careers of the German professors of law associated with the University of Wrocław between 1811 and 1945. Drawing on an analysis of professional biographies of the professors, the author points to those academic centres that accepted most of these scholars after they had finished their work in Wrocław. On the other hand, he indicates those universities from which most of the professors came to Wrocław in the first place. In addition, the author presents his opinion on the contention that the University of Wrocław was treated by German scholars as a “waiting room” before they left for a better university usually in Berlin.
Keywords: Uniwersytet Wrocławski; Wydział Prawa Uniwersytetu Wrocławskiego w latach 1811–1945; niemieccy profesorowie prawa; nauczanie prawa na Uniwersytecie Wrocławskim